(untitled) (Global Journals of Research in Engineering, 2020)
With the growth of cities, it is becoming increasingly necessary to expand the number of roads, consequently increasing the generation of environmental impacts. This article aims to verify the considerations about the negative and positive impacts caused by the pavement of the Highway BR-401 / RR. It has by methodology the application of questionnaire and case study, through a qualitative, exploratory approach of bibliographical and documentary character. It is concluded that the results obtained during the study are very relevant for the improvement of the duplication and restoration projects of BRs.